Analisis Desain dan Pembuatan untuk Alat Uji Shock Absorber Berbasis Mikrokontroler - Shobirin, Muchammad Ichwan; Irawan, Bambang (Badan Kerja Sama Teknik Mesin Indonesia, 2025)
A microcontroller is one of the most important electronic devices in the electronics industry. The research aims to design, develop and analyze innovative test devices to evaluate shock absorber performance. The test equipment is based on the use of microcontrollers and state-of-the-art sensor technology as well as providing accurate measurements and effective solutions to analyze shock absorber retardation characteristics. The process uses two variables, the time and the value of the deflection. There are two such variations that are used to carry out the data collection experiment on the shock absorber test device.The results of this study are expected to be able to provide real-time values or parameters on electronic devices for a national standard shock absorber test device capable of being an automatic reader for a good shock-absorber test.